2011
DOI: 10.1152/ajpcell.00465.2010
|View full text |Cite
|
Sign up to set email alerts
|

Activation characteristics of transient receptor potential ankyrin 1 and its role in nociception

Abstract: Transient receptor potential (TRP) ankyrin 1 (TRPA1) is a Ca(2+)-permeant, nonselective cationic channel. It is predominantly expressed in the C afferent sensory nerve fibers of trigeminal and dorsal root ganglion neurons and is highly coexpressed with the nociceptive ion channel transient receptor potential vanilloid 1 (TRPV1). Several physical and chemical stimuli have been shown to activate the channel. In this study, we have used electrophysiological techniques and behavioral models to characterize the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
52
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 65 publications
9
52
0
1
Order By: Relevance
“…Alternatively, the H 2 S-induced activation of TRPA1 receptors probably shares a common cellular mechanism that enhances the function of these chemosensitive and mechanosensitive receptors. Our observations gain support from findings showing that, in rodent dorsal root ganglion neurons, the activation of TRPA1 receptors by AITC enhanced the inward currents evoked by repeated applications of AITC (36) and by the mechanical stimulation of neurites (6). The cellular mechanisms by which TRPA1 activation leads to the sensitization of CSLV fibers is unclear, but they are probably related to changes in the membrane conductance or to the resting membrane potential (19), or both.…”
Section: Discussionsupporting
confidence: 84%
“…Alternatively, the H 2 S-induced activation of TRPA1 receptors probably shares a common cellular mechanism that enhances the function of these chemosensitive and mechanosensitive receptors. Our observations gain support from findings showing that, in rodent dorsal root ganglion neurons, the activation of TRPA1 receptors by AITC enhanced the inward currents evoked by repeated applications of AITC (36) and by the mechanical stimulation of neurites (6). The cellular mechanisms by which TRPA1 activation leads to the sensitization of CSLV fibers is unclear, but they are probably related to changes in the membrane conductance or to the resting membrane potential (19), or both.…”
Section: Discussionsupporting
confidence: 84%
“…Both brief NMM and AITC activated TRPA1 current when given prior to pBQN application but the currents remained at elevated levels despite washout. A similar Ca 21 -independent desensitization in response to NMM and AITC was recently noted by Raisinghani et al (2011). Figure 4C shows that TRPA1 channels activated by 50 mM NMM become desensitized after prolonged application.…”
supporting
confidence: 83%
“…TRPA1 is desensitized by Ca 21 entering the channel, although where it binds and its precise mechanism is unknown (Nagata et al, 2005;Wang et al, 2008). Recently, Raisinghani et al (2011) showed that continuous N-methylmaleimide (NMM) applications can desensitize TRPA1 channels in the absence of Ca 21 entry, suggesting a new type of desensitization. Here we show that pBQN acts as an electrophilic TRPA1 agonist, activating channels at low nanomolar concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Intrathecal injection of electrophilic TRPA1 activators has recently been reported to elicit thermal hyperalgesia and mechanical allodynia in mice and neuropathic rats [41][42][43] . Interestingly, pharmacological inhibition of spinal TRPA1 attenuated mechanical hypersensitivity in various rodent models of subacute and chronic pain [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Cation influx through TRPA1 also depolarizes the membrane and produces a sustained inhibition of voltage-gated sodium channels (naV), thereby reducing neuronal excitability and action potential-dependent neurotransmitter release. The net result of these actions is inhibition of C-fibre-evoked postsynaptic excitation, although TRPA1-mediated calcium influx may initially increase spontaneous excitatory postsynaptic currents via activation of ionotropic glutamate receptors (iGluR) 42,[49][50][51] . similar molecular mechanisms have been advanced to explain the antinociceptive effect of spinal TRPV1 activation 31,48 .…”
Section: Discussionmentioning
confidence: 99%